Pengaruh Teknologi terhadap Perilaku Masyarakat dalam Melakukan Judi Online di Desa Perk. Bukit Lawang Kecamatan Bahorok Kabupaten Langkat Provinsi Sumatera Utara - Manalu, Hendri Saputra; Mutriady, Anto; R, Rahmadany; Damanik, Janner; Syahputra, Deden (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
This community service activity addresses the topic “The Influence of Technology on Community Behavior in Engaging in Online Gambling in Perk. Bukit Lawang Village, Bahorok Subdistrict, Langkat Regency, North Sumatra Province.” The target audience for the legal counseling provided in this community service activity was the residents of Perk. Bukit Lawang Village, Bahorok Subdistrict, Langkat Regency, North Sumatra Province. This legal counseling aimed to educate the community about the dangers of engaging in online gambling. The community service activity was conducted at the Hall of the Perk. Bukit Lawang Village Office on Wednesday, January 21, 2026, from 9:00 a.m. to 12:00 p.m. WIB, with speakers consisting of lecturers from the Faculty of Law, Amir Hamzah University, Medan. The activity was attended by residents of Lubuk Cemara Village, the Subdistrict Head, and the Head of Perk. Bukit Lawang Village, Bahorok Subdistrict. The results of this community service activity indicate that many residents in Perk. Bukit Lawang Village engage in online gambling, predominantly men ranging from young to older age groups. The community expressed significant concern and a lack of knowledge about how to protect their families from online gambling. Therefore, through this socialization activity, it is expected that community understanding will increase in order to avoid and appropriately respond to the growing prevalence of online gambling.